Developmental biology of Meteorus pulchricornis parasitising painted apple moth - Chhagan, A.; Stephens, A.E.A.; Charles, J.G. (New Zealand Plant Protection, 2008)
Following the discovery of painted apple moth (PAM) Teia anartoides in Auckland in 1999 a longterm management programme was proposed in case eradication failed Research was initiated to evaluate the potential impact of natural enemies that were already present in New Zealand Laboratory bioassays determined the developmental biology of the larval parasitoid Meteorus pulchricornis on PAM at five constant temperatures (13 18 21 25 or 30 C) Total development time (egg to adult) ranged from 645 days at 13C to 160 days at 25C Meteorus pulchricornis adults provided with agarhoney parasitoid diet survived an average of 69 days and laid an average of 213 eggs at 21C Meteorus pulchricornis parasitised a significantly higher number of second and third instar PAM larvae compared to other larval instars The potential of M pulchricornis as a primary regulator of PAM populations in New Zealand is discussed